Too big to fail : the hazards of bank bailouts - Stern, Gary H.; Feldman, Ron J. (Brookings Institution Press, 2009)
The potential failure of a large bank presents vexing questions for policymakers. Failing banks are labeled 'too big to fail' (or TBTF). This book examines the issues surrounding TBTF, explaining why it is a problem and discussing ways of dealing with it